Ultimate Shear Resistance of Perfobond Rib Shear Connectors Based on a Modified Push-Out Test. Issue 4 (April 2013) - Wang, Zhenhai; Li, Qiao; Zhao, Canhui
This paper evaluates the ultimate shear resistance(USR) of the perfobond rib shear connector(PRSC) based on a modified push-out test and establishes a new equation for the USR. 33 modified push-out specimens were constructed and tested. The specimens had different perfobond bar diameters, perfobond rib hole diameters, concrete strengthes and transversal rebar quantities. From the test results, influencing factors of the USR such as the ultimate tensile capacity of perfobond bars, the shear stiffness of concrete dowels and the number of transversal rebar were evaluated experimentally. An new equation was developed based on regression analysis for the USR. This equation predicts the USR to within 14% of the experimental results in this test and the push-out tests for PRSC in pylon joint segments.